Intragenomic Long-Distance RNA–RNA Interactions in Plus-Strand RNA Plant Viruses - Chkuaseli, Tamari; White, K. Andrew (Frontiers in Microbiology, 2018)
Plant viruses that contain positive-strand RNA genomes represent an important class of pathogen. The genomes of these viruses harbor RNA sequences and higher-order RNA structures that are essential for the regulation of viral processes during infections. In recent years it has become increasingly evident that, in addition to locally-positioned RNA structures, long-distance intragenomic interactions, involving nucleotide base pairing over large distances, also contribute significantly to the control of various viral events. Viral processes that are modulated by such interactions include genome replication, translation initiation, translational recoding, and subgenomic mRNA transcription. Here we review the structure and function of different types of long-distance RNA-RNA interactions, herein termed LDRIs, present in members of the family Tombusviridae and other plus-strand RNA plant viruses.